Draft Genome of Lysinibacillus sphaericus Isolate 229C Pathogenic to Vector Mosquitoes - Afiannisa Viersanova; Hari Purwanto (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2021)
Lysinibacillus sphaericus is widely known as a bioinsecticide agent because it shows entomopathogenic activity against vector mosquitoes, especially of Culex and Anopheles spp. This bacterium known to have variations in toxicity. Its binary toxins, which is known to have a high toxicity, has a very low genetic variation, so that resistance problems has been reported. Therefore, exploration continues to be carried out to find a new effective and potential toxin to deal with the resistance problems. This study aims to analyze the genome of isolate 229C L. sphaericus, to identify the species of isolate 229C based on the 16S rRNA gene, and to identify toxin characteristics of the 229C isolate based on the results of genome sequence analysis. The 229C isolate was previously obtained from soil sample in Indonesia and showed a high pathogenicity against C. quenquefasciatus. Molecular identification was carried out with the 16S rRNA gene analysis. While draft genome and toxin analysis performed by conducting whole genome sequencing using Illumina Hiseq 2000, 250 bp pair-end protocol. The sequenced data then analized using freely available bioinformatics tools.The results of the molecular identification showed that the closest related species of isolate 229C was L. sphaericus. The isolate 229C has a genome size of 4.65 Mbp and G+C content of 36.83%. Toxin analysis showed that this isolate did not contain Mosquitocidal toxin (Etx/Mtx), binary toxin (Bin protein), crystal toxin (Cry48/Cry49 protein), nor Sphaericolysin genes. However, there are s-layer protein and hemolysin genes that also known to be associated with the toxicity of L. sphaericus to mosquitoes and possibly, are the answer to the problem of resistance to binary toxins. This result opens the opportunity for an analysis of the effectiveness of S-layer protein and Hemolysin against resistance population mosquitoes.